Challenges related to financial guarantee insurance - Schich, Sebastian (OECD Publishing, 2008)
Traditionally, bond insurers have provided guarantees of payments on municipal bonds, where defaults have been very limited. But since the late 1990s they have become increasingly involved as guarantors of elements of various structured financial products: in particular, the credit enhancements provided by these entities have played an important role in making securities based on sub-prime loans attractive to a wide range of investors. It is this trend change in their activity that has become the focal point in concerns about the health of these entities that have grown during the financial turbulence. The note identifies three policy issues that arise in the context of the current challenges facing these entities and it draws some preliminary findings. First, while concerns regarding the potential financial stability implications of further downgrades and/or failures of some of these companies have ebbed somewhat from their peaks in early 2008, the situation still bears monitoring. Second, current developments raise questions regarding the role of financial guarantors in specific financial market segments. In this context, there appears to be a public interest in the continued availability of guarantees on payments on municipal bonds. Private solutions seem to be forthcoming. Third, transparency of the financial guarantee insurance sector is limited. In this context, the performance of credit rating agencies in providing guidance for investors regarding the quality of the guarantees provided by financial guarantors appears to have been uneven
Keywords: Finance and Investment